STUDI KARAKTER MORFOLOGI DAN KANDUNGAN FENOL PADA SEPULUH GENOTIPE KEDELAI (Glycine max (L.) Merrill) - Iva Indrianingtyas; Mohammad Setyo Poerwoko (Jember University Press, 2020)
Soybean is one of the important food commodities for the people. Morphological characters are important to know about the seed potential, while the phenol content affected to the morphological characters of soybean. Research on the ten genotypes were expected to yield information about the seed that has the character of morphology and content of phenols most well so that the potential to generate the high production plant. This research was conducted with RAK (Randomized Block Design), using one treatment factor with ten genotypes (i.e. genotype one, genotype two, genotype three, genotype four, genotype five, Unej 1, Unej 2, Wilis, Malabar, and Ringgit). The data calculated using analysis of variance (Anova), and if the results expressed significantly different, then continued by using Scott Knott test (α 5%). The best seed selection, taken based on the morphological character (seed weight per plant 39,33 g/plant, weight of 100 seed 12,37 g/100 seed) and phenolic content 1,22 mg/g are genotype three. Keywords: Genotype, Morphologycal Character and Phenol Content